KRT17 as a prognostic biomarker for stage II colorectal cancer. (22nd November 2019) - Ujiie, Daisuke; Okayama, Hirokazu; Saito, Katsuharu; Ashizawa, Mai; Thar Min, Aung Kyi; Endo, Eisei; Kase, Koji; Yamada, Leo; Kikuchi, Tomohiro; Hanayama, Hiroyuki; Fujita, Shotaro; Sakamoto, Wataru; et al.
Abstract: Adjuvant chemotherapy is considered for patients with stage II colorectal cancer (CRC) characterized by poor prognostic clinicopathological features; however, current stratification algorithms remain inadequate for identifying high-risk patients. To develop prognostic assays, we conducted a step-wise screening and validation strategy using nine cohorts of stage II patients based on multiple platforms, including microarray, RNA-sequencing (RNA-seq) and immunohistochemistry (IHC) on formalin-fixed paraffin-embedded (FFPE) tissues. Four microarray datasets (total n = 458) were used as the discovery set to screen for single genes associated with postoperative recurrence. Prognostic values of candidate genes were evaluated in three independent microarray/RNA-seq validation cohorts ( n = 89, n = 93 and n = 183, respectively), and then IHC for KRT17 was conducted in two independent FFPE series ( n = 110 and n = 44, respectively). We found that high levels of KRT17 transcript expression were significantly associated with poor relapse-free survival (RFS) not only in the discovery set, but also in three validation cohorts, and its prognostic impact was independent of conventional factors by multivariate analyses. Positive staining of KRT17 protein was significantly associated with poor RFS in two independent FFPE cohorts. KRT17 protein expression had independent prognostic impact on RFS in a multivariate model adjusted for conventional variables, including high-risk clinicopathological features. In conclusion, using nine independent cohorts consisting of 997 stage II patients, we identified and validated the expression of KRT17 transcript and KRT17 protein as a robust prognostic biomarker that can discriminate postoperative stage II patients who are at high probability of disease recurrence, providing additional prognostic stratification beyond the currently available high-risk factors. Abstract : This study analyzed nine independent cohorts of postoperative patients with stage II colorectal cancer, demonstrating that KRT17 immunohistochemistry can add additional discriminative value to identify stage II patients at high probability of recurrence, beyond conventional 'high-risk' characteristics.